FRI0179 Infliximab infusion reactions in patients with rheumatoid arthritis and spondylarthropathies. (23rd January 2014) - Markatseli, T. E.; Migkos, M.; Somarakis, G.; Voulgari, P. V.; Drosos, A. A.
Abstract : Background: Therapies that target TNF have been successfully used for the treatment of patients with rheumatoid arthritis (RA) and spondylarthropathies (SpA). TNF-α blocking agents have been relatively safe, however intravenous administration of infliximab is associated with increased rates of infusion allergic reactions (IAR). Objectives: To describe infusion reactions in patients with RA and SpA under infliximab therapy. Methods: In the present retrospective observational study we reviewed the data of 335 patients with RA (थ=157) or SpA (थ=178, 104 with ankylosing spondylitis and 74 with psoriatic arthritis) who commenced infliximab therapy at the time period from January 2000 till May 2012. Patients' data were reviewed for the entire period of infliximab therapy till the discontinuation of the treatment for any reason. Patients who continue infliximab therapy had a last follow-up on August 2012. The following parameters were recorded: type of IAR (acute or delayed), time of occurrence, severity, symptoms, management of symptoms, whether the reaction leaded to permanent discontinuation of infliximab, the number of infusion reactions per patient, as well as concomitant use of disease modifying anti-rheumatic drugs (DMARDs). Results: All 335 patients were evaluated for IAR in a total of 10408 infliximab infusions (range 1-88 infusions/ RA patient and 1-91 infusions/ SpA patient). One hundred and thirty-two IAR were recorded (70 in RA patients and 62 in SpA patients). The incidence of IAR was 1.5% in RA patients and 1.1% in SpA patients, while the incidence of severe reactions was 0.7% and 0.4%, respectively (p=0.163). In total, 51 (32.5%) RA patients and 45 (25.3%) SpA patients experienced 1 or more infusion reactions (p=0.193). The majority of the IAR were acute (RA: 94.3% vs SpA: 100%, p=0.161) and of mild to modest severity (RA: 80% vs SpA: 71%, p=0.315). 56 patients were withdrawn due to IAR [31 (19.7%) RA patients vs 25 (14.0%) SpA patients, p=0.212]. The majority of these adverse events were noticed the first 3 and 2 years from the initiation of infliximab treatment in RA and SpA patients, respectively. Interestingly, 22.6% and 0.04% of the severe IAR which demanded the permanent discontinuation of infliximab occurred after the 4 th year of treatment in RA and SpA patients, respectively (p=0.05). Of note, the respective percentages of RA patients who received or no concomitant methotrexate (MTX) and experienced an IAR in comparison was 27.7% and 45.5% (p=0.05). Conclusions: The risk of infliximab IAR was relatively low in our RA and SpA patients. Although most IAR were mild to moderate and occurred early during the first years of infliximab treatment, severe IAR occurred in RA patients after 4 or more years of treatment but not in SpA patients. Concomitant use of methotrexate may reduce the risk of IAR in RA patients. Disclosure of Interest: None Declared